Determination of relationship between milk production and the quality of embryo of donor cows - AYASAN, TUGAY; HIZLI, HATICE; ÇAMLIDAG, AYSUN; KARA, UGUR; GÖK, KURTULUS; KARAKOZAK, EMEL; ÇOBAN, SERDAL; MUTLU, HASAN; KILIÇALP, NUMAN; SEGMENOGLU, MANSUR SEYMEN (The Indian Journal of Animal Sciences, 2011)
The relationship between milk production in donor cows (74) and quality of embryos was examined in the experiment. According to their milk production, the donors were divided into three groups. In the group 1 there were 18 donors with the milk yield lower than 5000 kg per lactation; in group 2, 32 donors, with milk yield between 5000 kg and 7000 kg, and in group 3, 24 donors with milk production over 7000 kg. Number of total embryos and percentage of transferable embryos in groups were statistically significant. The higher rate of non-transferable embryos was recorded in donors in group 3 with high milk production (48.91%). A positive correlation was recorded between the number of total embryos suitable for transfer decreased in cows with higher milk production (r =-0.267), and an important correlation was recorded (r = -0.070) between milk production and transferable embryo number.